Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1039/d2fo03900a
|View full text |Cite
|
Sign up to set email alerts
|

Effect of kimchi intake on body weight of general community dwellers: a prospective cohort study

Abstract: Long-term moderate kimchi intake (about 2–3 servings per day), mainly of baechu (cabbage) kimchi, was associated with weight loss in middle-aged and older Koreans, especially men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…A previous RCT involving 22 patients with obesity showed that both fresh kimchi (1-day-old kimchi) and fermented kimchi (10-day-old kimchi) significantly reduced body weight, BMI and body fat, and fermented kimchi consumption decreased waist-to-hip ratio, total cholesterol and leptin levels 20. In a cohort study of 20 066 participants with obesity aged 40–69 years old, the average intake of kimchi of 2–3 servings/day was associated with changing to a normal weight group 34. This may be because the white rice and kimchi dietary pattern is characterised by high consumption of processed food.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous RCT involving 22 patients with obesity showed that both fresh kimchi (1-day-old kimchi) and fermented kimchi (10-day-old kimchi) significantly reduced body weight, BMI and body fat, and fermented kimchi consumption decreased waist-to-hip ratio, total cholesterol and leptin levels 20. In a cohort study of 20 066 participants with obesity aged 40–69 years old, the average intake of kimchi of 2–3 servings/day was associated with changing to a normal weight group 34. This may be because the white rice and kimchi dietary pattern is characterised by high consumption of processed food.…”
Section: Discussionmentioning
confidence: 99%
“…20 In a cohort study of 20 066 participants with obesity aged 40-69 years old, the average intake of kimchi of 2-3 servings/day was associated with changing to a normal weight group. 34 This may be because the white rice and kimchi dietary pattern is characterised by high consumption of processed food. In the results of the scoping review including two RCT studies, intake of fresh kimchi (before fermented) showed a decrease in WCs and body fat percentage.…”
Section: Discussionmentioning
confidence: 99%